THE EFFECT OF TEMPEH EXTRACT GEL ON WOUND HEALING IN DIABETES RAT: OVERVIEW OF TISSUE COLLAGEN, WOUND CLOSURE, EPITHELIALIZATION AND CAPILLARIZATION - Ignasius Adi Kurniawan; Rini Dwiastuti; Sri Hartati Yuliani (Sanata Dharma University, 2020)
The development of wound healing preparations in diabetes conditions needs to be done because the wound healing process in the respective conditions requires longer time. The aim of this study is to measure the effect of tempeh extract gel containing genistein on wound healing in diabetes rats by observing the response parameters of collagen expression, wound closure speed, epithelialization, and capillarization of wound tissue. The results of testing wound closure using a base gel treatment, tempeh extract gel 2.5%, 5%, 7.5% and without treatment indicated that the treated groups of tempeh extract gel 5% and 7.5% have significant effect on diabetes wound healing in the tested animals. This indication is strengthened by the results of the non-treatment groups statistical test with the 5% and 7.5% tempeh extract gel treatment which showed significant difference in influencing the wound closure response, epithelialization and collagen formation in tissue. The results of the statistical in group without treatment with the base treatment group without extract gel and tempeh extract gel 2.5% showed no significant difference in influencing the wound closure response, epithelialization and collagen formation. Statistical test results on capillarization responses indicated that the results were not significantly different from all treatment groups.